2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649454
|View full text |Cite
|
Sign up to set email alerts
|

A structured approach to requirements gathering creation using PaJMa Models

Abstract: The process of preparation for request for proposals for health information systems typically results in missed opportunities for improvements due to the technical focus of traditional requirements gathering processes. The increased integration of health care systems between wards and external supporting agencies, reliance on professional practice guidelines, and needs for cultural sensitivities requires a specialized method for requirements gathering. We explore the use of a patient journey modeling approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…At the end of the table-top exercise, we collected twenty eight (28) filled and four (4) blank questionnaires (thirty two (32) in total). At the end of the table-top exercise, we collected twenty eight (28) filled and four (4) blank questionnaires (thirty two (32) in total).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the table-top exercise, we collected twenty eight (28) filled and four (4) blank questionnaires (thirty two (32) in total). At the end of the table-top exercise, we collected twenty eight (28) filled and four (4) blank questionnaires (thirty two (32) in total).…”
Section: Resultsmentioning
confidence: 99%
“…Further clinical (reference) process models are presented in [30], [31], [32], [33], [34]. In [35] the authors present a modeling approach, which introduces principles of process modeling in healthcare using EPCs and employ these principles to existing medical information systems by implementing them using a Workflow Management System (WFMS).…”
Section: Related Workmentioning
confidence: 99%
“…The Patient Journey Modeling Architecture (PaJMa) -as another approachfocuses especially the patient flow. It focuses on the patient's movement through a health care organization and on providing a visual representation of the processes involved in a patient journey [18]. The Breakthrough Series Model for Improvement (MOI), developed by the Institute of Healthcare Improvement (IHI) in U.S., is another patient flow based approach initially developed for manufacturing and business domain.…”
Section: Related Workmentioning
confidence: 99%
“…Although various modeling techniques are being used in support of quality improvement and technology adoption, there remains an issue of whether those affected by the organizational change are able to assess the potential impact based on how the information is represented. In our earlier research [ 36 ], we have demonstrated the difference when 2 modeling techniques are used to represent the same patient journey from a functional matrix perspective. This paper presents a comparison of 5 process modeling techniques with a focus on supporting HIT integration into clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The Patient Journey Modeling Architecture (PaJMa) is a patient journey modeling methodology that enables a visual representation of the interaction of processes, technologies, and people used to support a patient’s experience in the health care system [ 9 , 36 ]. This modeling technique represents the following layers: staff roles, processes, information creation/movement, HIT, IT infrastructure, patient needs/practice guidelines/policies, and metrics [ 51 ] (refer to Figure 1 for an example).…”
Section: Introductionmentioning
confidence: 99%